The Price of Security: On the Causality and Impact of Lay-off Risks on Wages - Stefan Arent; Wolfgang Nagl (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2011)
We examine the impact of lay-off risks on wages. Portfolio as well as search theoreticmodelling predicts higher exogenous lay-off risks to go along with higher wages. But,an impact of wages on lay-off risks (e.g., endogenous job destruction) is also plausible.Using the German BA Employment Panel (2008), we estimate a wage equation withexogenous lay-off risks for the most important industries in West Germany. We addressthe mutual causality by controlling for endogeneity via an instrumental variableapproach. Furthermore, we restrict our analysis to the high skilled to avoid a highimpact on tariff commitment. Our findings suggest the presence of risk premiums inthree of five industries. The level of impact and its significance depends on the industryand on the gender of the employee.
Keywords: I31; J63; 330; Lay-off risk; wages; Kündigung; Risiko; Lohnstruktur; Arbeitsplatzsicherung; Hochqualifizierte Arbeitskräfte; Schätzung; Deutschland